The Influence of Market Orientation and Product Innovation on Marketing Performance Through Competitive Advantage as an Intervening Variable in the Snack Household Industry in Sukabumi Regency - Dwi Gemina; Palahudin; Siti Juwita Nurastri Mustika (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of market orientation, product innovation on marketing performance through competitive advantage as an intervening variable in the snack household industry in Sukabumi Regency. This research method uses a quantitative approach with primary data obtained through a questionnaire with the Likert scale. The population in this study is snack business actors in Sukabumi Regency with sampling techniques using purposiv sampling. The number of samples used in this study was 250 business actors. Data analysis was carried out using the Statistical Product and Service Solution (SPSS) method. The results of the study show that market orientation and product innovation have a positive and significant effect on marketing performance, market orientation and product innovation have a positive and significant effect on marketing performance through competitive advantage.